Targeting pancreatic and ovarian carcinomas using the auristatin-based anti-CD70 antibody–drug conjugate SGN-75 - Ryan, M C (Nature Publishing Group, 2010)
BACKGROUND: CD70 is an ideal target for antibody-based therapies because of its aberrant high expression in renal carcinomas and non-Hodgkin lymphomas and its highly restricted expression in normal tissues. The expression profiling of CD70 in carcinomas has been limited because of the lack of a CD70-specific reagent that works in formalin-fixed paraffin-embedded (FFPE) tissues. METHODS: We generated murine monoclonal antibodies (mAbs) specific for CD70 and validated their specificity by western blot analysis and developed a protocol for immunohistochemistry on FFPE tissues. CD70+ tumour cell lines were used for testing the anti-tumour activity of the anti-CD70 antibody–drug conjugate, SGN-75. RESULTS: We report novel detection of CD70 expression in multiple cancers including pancreatic (25%), larynx/pharynx (22%), melanoma (16%), ovarian (15%), lung (10%), and colon (9%). Our results show that pancreatic and ovarian tumour cell lines, which express high levels of endogenous or transfected CD70, are sensitive to the anti-tumour activity of SGN-75 in vitro and in vivo. CONCLUSION: Development of murine mAbs for robust and extensive screening of FFPE samples coupled with the detection of anti-tumour activity in novel indications provide rationale for expanding the application of SGN-75 for the treatment of multiple CD70 expressing cancers.